Pengaruh Penempatan Kerja, Pelatihan Kerja, Dan Lingkungan Kerja Non Fisik Terhadap Kepuasan Kerja Pegawai Pada Kantor Camat Masbagik - Rina Putri Rahayu; Sulaimiah Sulaimiah (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
This research aims to analyze the influence of job placement, job training, and non-physical work environment on employee job satisfaction at the Masbagik sub-district office. The type of research used is causal associative research. The data analysis technique used was Multiple Linear Regression using IBM SPSS version 26. The respondents in this study were all 43 employees of the Masbagik Subdistrict Office. The results of the analysis show that: (1) Job Placement has a positive and significant effect on Job Satisfaction of Masbagik Subdistrict Office Employees (2) Job Training has a positive and significant effect on Job Satisfaction of Masbagik Subdistrict Office Employees (3) Non-Physical Work Environment has a positive and insignificant effect on Job Satisfaction of Masbagik Subdistrict Office Employees